Perspective on Micro-Supercapacitors - Sun, Xiangfei; Chen, Kunfeng; Liang, Feng; Zhi, Chunyi; Xue, Dongfeng (Frontiers in Chemistry, 2022)
The rapid development of portable, wearable, and implantable electronic devices greatly stimulated the urgent demand for modern society for multifunctional and miniaturized electrochemical energy storage devices and their integrated microsystems. This article reviews material design and manufacturing technology in different micro-supercapacitors (MSCs) along with devices integrate to achieve the targets of their various applications in recent years. Finally, We also critically prospect the future development directions and challenges of MSCs.